Analysis of Economic Development Business Model For Pesantren Independence: (Study at Pesantren Cendekia Amanah, Depok City) - Sodik, Sodik; Ayuniyyah, Qurroh; Supriyanto, Trisiladi (Al-Infaq: Jurnal Ekonomi Islam, 2025)
Pesantren Cendekia Amanah is a pesantren that was established five years ago, precisely in 2019. As an institution located within the community, this pesantren plays a significant role and contributes to the education system, socio-cultural aspects, and economic development. In order to develop the pesantren's economic self-sufficiency, Pesantren Cendekia Amanah has established facilities that can be utilized to develop the existing business units within the pesantren. This research aims to identify the economic business model developed by the pesantren and the implications of these businesses in efforts to enhance economic self-sufficiency at the pesantren. The data collection techniques used in this research include three methods: observation, interviews, and documentation. The data analysis method used in this research is the interactive model of Miles and Huberman. According to their view, data analysis generally consists of three concurrent activities: data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the business model developed by Pesantren Cendekia Amanah has a significant impact on increasing the economic self-sufficiency of the pesantren.